Gadolinium-containing carbon dot composite nanomaterial and preparation method thereof
By preparing the carbon -containing composite nanomaterials, the problem of the GD3+leakage of the cricket -based magnetic resonance film creation agent is solved, and the efficient nuclear magnetic resonance imaging and fluorescent imaging are achieved, which is suitable for biomedical imaging and material degradation monitoring.
Patent Information
- Application Number
- CN202411517572.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, gadolinium-based magnetic resonance contrast agents have a risk of Gd3+ leakage, resulting in neurotoxicity and renal dysfunction, and imaging technology has limitations, making it difficult to accurately evaluate burn injuries.
Adopt a preparation method of carbon -containing composite nanomaterials. By dissolving salt and phthalamine in ionic water, heating reactions by polytetrafluoroethylene reaction kettle, and then microfotic filter membrane filtering and dialysis bag dialysis pouring dialysis bag , Finally frozen and dry treatment, get brown -yellow powder -like carbon points.
This material enhances the magnetic response capacity and biocompatibility through the composite of the cricket and the carbon point, reduces the leakage of GD3+, improves the effect of nuclear magnetic resonance, and has fluorescent imaging capabilities. It is suitable for biomedical imaging and material degradation monitoring.
Smart Images

Figure CN119367561A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite biomaterials, and in particular to a gadolinium-containing carbon dot composite nanomaterial and a preparation method thereof. Background Art
[0002] Wound healing can generally be divided into four intersecting processes, namely hemostasis, inflammation, proliferation, and extracellular matrix remodeling. Surgical intervention and real-time monitoring of different stages of wound healing are very important for successful wound healing. For complex wounds, especially burn wounds, accurate assessment is complex and difficult. Researchers have proposed a variety of imaging methods to assess burn injuries, including commonly used CT imaging, magnetic resonance imaging, and ultrasound imaging, as well as some emerging imaging technologies, such as hyperspectral imaging, unilateral magnetic resonance imaging, and laser Doppler perfusion imaging. These imaging technologies can largely assist in understanding the depth and range of burns, but a single imaging technology has certain limitations. For example, the extensive use of X-ray radiation in CT imaging may cause renal damage, ultrasound imaging has the disadvantages of limited one-time detection range and narrow probe, and laser Doppler perfusion imaging may lead to inaccurate assessment of burn wounds. Therefore, the application of multimodal imaging technology can combine the advantages of multiple technologies at the same time, monitor the status of implanted materials in situ and monitor the degradation of materials, which is helpful for clinical diagnosis and treatment.
[0003] Magnetic resonance imaging (MRI) is a non-invasive high-resolution imaging technology that has been widely used in clinical diagnosis. Gadolinium has the largest number of unpaired electrons in the periodic table and is the most ideal T1 imaging contrast agent. So far, at least 9 types of gadolinium-based MRI contrast agents have been approved for human MRI. 3+ It has certain toxicity, so gadolinium-based contrast agents usually exist in the form of complexes. However, some gadolinium-based complexes also have Gd 3+ The risk of Gd leakage can cause certain neurotoxicity, especially causing nervous system fibrosis in patients with renal dysfunction. 3+ One of the ways to leak is to transfer Gd 3+ Encapsulated into inorganic nanoparticle carriers, such as semiconductor quantum dots, silica, calcium fluoride and ferroferric oxide nanoparticles. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a gadolinium-containing carbon dot composite nanomaterial and a preparation method thereof to solve the problems in the prior art.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is: a method for preparing a gadolinium-containing carbon dot composite nanomaterial, comprising the following steps:
[0006] S1: dissolving gadolinium salt and o-phenylenediamine in deionized water to form a mixed solution, and stirring at room temperature for 30 to 60 minutes to make the solution uniform;
[0007] S2: adding the uniformly mixed solution into a polytetrafluoroethylene reactor and heating it to react, and naturally cooling the solution after the reaction to room temperature to obtain a product solution;
[0008] S3: The product solution is filtered with a microporous filter membrane in turn, and then dialyzed with a dialysis bag to remove unreacted small molecules, and then freeze-dried to obtain brown-yellow powder-containing gadolinium carbon dots.
[0009] The beneficial effects of the present invention are as follows: gadolinium, as a rare earth element, has good paramagnetism or superparamagnetism. After being compounded with carbon dots, it can give the composite material excellent magnetic response ability. This magnetic property makes the material useful in biomedical fields such as magnetic resonance imaging and targeted drug delivery. As an emerging zero-dimensional carbon material, carbon dots have ultra-small size and good biocompatibility, which can not only isolate the environment from Gd 3+ interference, ensuring excellent T1 contrast effect and effectively reducing Gd 3+ The leak is Gd 3+ Excellent nanocarriers, their small size facilitates rapid clearance from the body. Another unique advantage of carbon dots is that they have excitation wavelength-dependent fluorescence properties and excellent photostability, and are widely used in biomedical fluorescence imaging. Fluorescence imaging can be used to monitor biological functions and pathological processes in real time, such as inflammatory processes, cardiovascular diseases, and material degradation, due to its non-invasiveness, high sensitivity, and high spatiotemporal resolution.
[0010] In step S1, gadolinium salt and o-phenylenediamine are dissolved in deionized water and stirred sufficiently to ensure uniform dispersion of the reactants and provide good conditions for subsequent reactions.
[0011] In step S2, a polytetrafluoroethylene reactor is used for heating reaction. The equipment provides a stable and controllable environment for the reaction due to its excellent high temperature resistance and corrosion resistance. By precisely controlling the reaction temperature and time, the reaction kinetics can be optimized, promoting the effective combination between gadolinium ions and carbon dot precursors (such as intermediates derived from o-phenylenediamine), thereby generating high-quality gadolinium-containing carbon dot composite nanomaterials. The process of natural cooling to room temperature helps to reduce the internal stress of the material caused by sudden temperature changes, further improving the stability of the product.
[0012] The purification process in step S3 includes microporous membrane filtration and dialysis bag dialysis. The microporous membrane can effectively remove large particle impurities in the solution, while the dialysis bag further removes unreacted small molecules and low molecular weight components in the solvent through the size exclusion effect. Subsequently, the water in the product is removed by low-temperature vacuum drying, retaining its original structure and properties, and finally obtaining brown-yellow powder containing gadolinium carbon dots, which is easy to store and use.
[0013] Furthermore, in the above method for preparing the gadolinium-containing carbon dot composite nanomaterial, the gadolinium salt in S1 is gadolinium chloride hexahydrate.
[0014] The beneficial effect of adopting the above further scheme is that gadolinium chloride hexahydrate has good solubility in water, which is conducive to full mixing with reactants such as o-phenylenediamine and promotes uniform reaction.
[0015] Furthermore, in the above method for preparing the gadolinium-containing carbon dot composite nanomaterial, the gadolinium salt concentration of the mixed solution in S1 is 6.2 mg / mL, and the o-phenylenediamine concentration of the mixed solution is 12.6 mg / mL.
[0016] Furthermore, in the above method for preparing the gadolinium-containing carbon dot composite nanomaterial, the heating temperature in S2 is 160° C. and the reaction time is 6 hours.
[0017] Furthermore, in the above method for preparing the gadolinium-containing carbon dot composite nanomaterial, the pore size of the microporous filter membrane in S3 is 0.22 μm; the molecular weight of the dialysis bag is 500 Da, and the dialysis time is 3 days.
[0018] Furthermore, a gadolinium-containing carbon dot composite nanomaterial is prepared by the above preparation method, wherein the particle size of the gadolinium-containing carbon dot composite nanomaterial is 1.2-1.4 nm, and under the excitation of light with a maximum excitation wavelength of 418 nm, bright yellow fluorescence can be emitted, and the maximum emission wavelength is 566 nm.
[0019] The beneficial effects of the present invention are as follows: the gadolinium-containing carbon dot composite nanomaterial is composed of gadolinium with excellent nuclear magnetic resonance imaging performance and carbon dots with good biocompatibility, and a nuclear magnetic resonance / fluorescence dual-modality imaging nanoplatform is constructed. The combination of gadolinium and carbon dots enhances the nuclear magnetic resonance imaging effect of gadolinium, and obtains a better nuclear magnetic resonance imaging effect than Gd 3+ The higher longitudinal relaxation rate, excellent fluorescence properties and photostability of carbon dots make them suitable for applications in bioimaging and monitoring of stent degradation.
[0020] Gadolinium-containing carbon dots have unique fluorescence properties. Under light excitation of 350-500nm, they emit bright yellow fluorescence with a maximum emission wavelength of 566nm. The emission wavelength remains almost unchanged with the increase of excitation wavelength, which proves that they have good photostability. In addition, the gadolinium-containing carbon dots have excellent biocompatibility and can be used for in vivo and in vitro fluorescence imaging, as well as for monitoring material degradation.
[0021] The preparation process of gadolinium-containing carbon dot composite nanomaterials is reasonably designed and easy to operate. The gadolinium-containing carbon dot composite nanomaterials not only have nuclear magnetic resonance / fluorescence dual-modal imaging capabilities, but also have good biocompatibility and have great clinical application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The transmission electron microscope image of the gadolinium-containing carbon dots obtained in Example 1 and the high-resolution transmission electron microscope image of the gadolinium-containing carbon dots obtained;
[0023] Figure 2 is a Fourier transform infrared (FT-IR) spectrum of the gadolinium-containing carbon dots obtained in Example 1;
[0024] Figure 3 High-resolution transmission electron microscope images and element distribution maps of carbon dots and gadolinium-containing carbon dots obtained in Example 1;
[0025] Figure 4 for Figure 3 The element distribution histogram in ;
[0026] Figure 5 The fluorescence emission spectra of the gadolinium-containing carbon dots obtained in Examples 1 to 5 and the carbon dots obtained in the comparative example under 418 nm light excitation;
[0027] Figure 6 The UV-visible absorption spectrum, the fluorescence emission spectrum under 418 nm light excitation, and the excitation spectrum at an emission wavelength of 566 nm of the gadolinium-containing carbon dots obtained in Example 1 are shown;
[0028] Figure 7 The gadolinium-containing carbon dots and different concentrations of Gd obtained in Example 1 3+ T1-weighted imaging and Gd 3+ Longitudinal relaxivity test with gadolinium-containing carbon dots in ultrapure water;
[0029] Figure 8 The fluorescence photos of the gadolinium-containing carbon dots obtained in Example 1 after being doped with the polymer film in PBS solution at different time points;
[0030] Fig. 9 for Figure 8 Schematic diagram of the changes in fluorescence intensity;
[0031] Fig.10 For different concentrations of Gd 3+ The cell survival rate after co-culture with rat calvarial osteoblasts (ROBs) and the cell survival rate after co-culture of the carbon dots obtained in Example 1 and the gadolinium-containing carbon dots with ROBs;
[0032] Fig.11 This is the imaging image of the gadolinium-containing carbon dots on ROBs cells obtained in Example 1 under a fluorescent inverted microscope;
[0033] Fig.12 This is the imaging image of the gadolinium-containing carbon dots on ROBs cells obtained in Example 1 under a laser confocal microscope;
[0034] Fig.13 This is the imaging image of zebrafish larvae by gadolinium-containing carbon dots obtained in Example 1;
[0035] Fig.14 The three-dimensional imaging image of zebrafish larvae by gadolinium-containing carbon dots obtained in Example 1; DETAILED DESCRIPTION
[0036] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0037] Embodiment 1:
[0038] A method for preparing a gadolinium-containing carbon dot composite nanomaterial comprises the following steps:
[0039] Step 1: Weigh 1 mmol of gadolinium chloride hexahydrate and 7 mmol of o-phenylenediamine and dissolve them in 60 mL of deionized water, stirring for 1 hour to fully dissolve;
[0040] Step 2: adding the mixed solution into a polytetrafluoroethylene reactor, reacting at 160° C. for 6 hours, and naturally cooling to room temperature to obtain a product solution;
[0041] Step 3: The product solution was filtered through a microporous filter membrane with a pore size of 0.22 μm, and dialyzed for 3 days using a dialysis bag with a molecular weight of 500 Da to remove unreacted small molecules, followed by freeze-drying to obtain brown-yellow powdery gadolinium-containing carbon dots.
[0042] Embodiment 2:
[0043] A method for preparing a gadolinium-containing carbon dot composite nanomaterial comprises the following steps:
[0044] Step 1: Weigh 2 mmol of gadolinium chloride hexahydrate and 7 mmol of o-phenylenediamine and dissolve them in 60 mL of deionized water, stirring for 1 hour to fully dissolve;
[0045] Step 2: adding the mixed solution into a polytetrafluoroethylene reactor, reacting at 160° C. for 6 hours, and naturally cooling to room temperature to obtain a product solution;
[0046] Step 3: The product solution was filtered through a microporous filter membrane with a pore size of 0.22 μm, and dialyzed for 3 days using a dialysis bag with a molecular weight of 500 Da to remove unreacted small molecules, followed by freeze-drying to obtain brown-yellow powdery gadolinium-containing carbon dots.
[0047] Embodiment 3:
[0048] A method for preparing a gadolinium-containing carbon dot composite nanomaterial comprises the following steps:
[0049] Step 1: Weigh 3 mmol of gadolinium chloride hexahydrate and 7 mmol of o-phenylenediamine and dissolve them in 60 mL of deionized water, stirring for 1 hour to fully dissolve;
[0050] Step 2: adding the mixed solution into a polytetrafluoroethylene reactor, reacting at 160° C. for 6 hours, and naturally cooling to room temperature to obtain a product solution;
[0051] Step 3: The product solution was filtered through a microporous filter membrane with a pore size of 0.22 μm, and dialyzed for 3 days using a dialysis bag with a molecular weight of 500 Da to remove unreacted small molecules, followed by freeze-drying to obtain brown-yellow powdery gadolinium-containing carbon dots.
[0052] Embodiment 4:
[0053] A method for preparing a gadolinium-containing carbon dot composite nanomaterial comprises the following steps:
[0054] Step 1: Weigh 4 mmol of gadolinium chloride hexahydrate and 7 mmol of o-phenylenediamine and dissolve them in 60 mL of deionized water, stirring for 1 hour to fully dissolve;
[0055] Step 2: adding the mixed solution into a polytetrafluoroethylene reactor, reacting at 160° C. for 6 hours, and naturally cooling to room temperature to obtain a product solution;
[0056] Step 3: The product solution was filtered through a microporous filter membrane with a pore size of 0.22 μm, and dialyzed for 3 days using a dialysis bag with a molecular weight of 500 Da to remove unreacted small molecules, followed by freeze-drying to obtain brown-yellow powdery gadolinium-containing carbon dots.
[0057] Embodiment 5:
[0058] A method for preparing a gadolinium-containing carbon dot composite nanomaterial comprises the following steps:
[0059] Step 1: Weigh 6 mmol of gadolinium chloride hexahydrate and 7 mmol of o-phenylenediamine and dissolve them in 60 mL of deionized water, stirring for 1 hour to fully dissolve;
[0060] Step 2: adding the mixed solution into a polytetrafluoroethylene reactor, reacting at 160° C. for 6 hours, and naturally cooling to room temperature to obtain a product solution;
[0061] Step 3: The product solution was filtered through a microporous filter membrane with a pore size of 0.22 μm, and dialyzed for 3 days using a dialysis bag with a molecular weight of 500 Da to remove unreacted small molecules, followed by freeze-drying to obtain brown-yellow powdery gadolinium-containing carbon dots.
[0062] Comparative Example:
[0063] A method for preparing yellow light carbon dots comprises the following steps:
[0064] Step 1: Weigh 7 mmol of o-phenylenediamine and dissolve it in 60 mL of deionized water. Stir for 1 hour to fully dissolve.
[0065] Step 2: adding the mixed solution into a polytetrafluoroethylene reactor, reacting at 160° C. for 6 hours, and naturally cooling to room temperature to obtain a product solution;
[0066] Step 3: The product solution was filtered through a microporous filter membrane with a pore size of 0.22 μm, and dialyzed for 3 days using a dialysis bag with a molecular weight of 500 Da to remove unreacted small molecules, and then freeze-dried to obtain brown-yellow powdered carbon dots.
[0067] Experimental test analysis:
[0068] The gadolinium-containing carbon dots prepared in this example were used as test samples for analysis and property inspection.
[0069] The gadolinium-containing carbon dot composite nanomaterials prepared in Examples 1 to 5 were characterized by ultraviolet visible light absorption spectra (UV-vis) and fluorescence spectra (PL). Figure 5 As shown, the gadolinium-containing carbon dots prepared in Examples 1 to 5 can obtain a maximum emission peak of 566 nm under the excitation of 418 nm. It can be seen that with the increase of the gadolinium feed amount, the fluorescence intensity of the gadolinium-containing carbon dots gradually decreases, indicating that the introduction of gadolinium will inhibit the fluorescence intensity of the carbon dots to a certain extent. Therefore, in order to ensure that gadolinium is introduced under the condition of the weakest influence on the fluorescence intensity of the carbon dots, the raw material ratio in Example 1 is selected for the next step of the experiment.
[0070] like Figure 6As shown in the figure, the UV-visible absorption spectrum of the gadolinium-containing carbon dots obtained in Example 1, the fluorescence emission spectrum under 418nm light excitation, and the excitation spectrum at an emission wavelength of 566nm, the inset is a photo of it under natural light (left) and a photo of it emitting yellow fluorescence under 418nm laser irradiation (right). The UV-visible absorption spectrum of the gadolinium-containing carbon dots prepared in Example 1 has a strong absorption peak at 205nm, which belongs to the π-π* transition of the aromatic C=C bond in the gadolinium-containing carbon dots. In addition, there is a shoulder peak at 430nm. According to previous literature reports, the absorption peak at 440nm proves the presence of poly-o-phenylenediamine groups, so we speculate that the absorption peak at 430nm here can be attributed to the poly-o-phenylenediamine groups present in the gadolinium-containing carbon dots. We speculate that in the formation process of gadolinium-containing carbon dots, o-phenylenediamine is first oxidized to poly-o-phenylenediamine oligomers, which aggregate to form carbon core centers through dehydration and carbonization. The carbon core centers eventually form complete carbon cores, and then the connections between the carbon cores are destroyed to form carbon dots.
[0071] The gadolinium-containing carbon dots prepared in Example 1 were characterized by transmission electron microscopy. The characterization results are as follows: Figure 1 , Figure 3 and Figure 4 shown. Figure 1 Divided into Figure 1 a and Figure 1 b, Figure 1 a is a transmission electron microscope image of the gadolinium-containing carbon dots obtained in Example 1, wherein the inset is a particle size distribution diagram of the gadolinium-containing carbon dots obtained in Example 1; Figure 1 b is a high-resolution transmission electron microscope image of the gadolinium-containing carbon dots obtained in Example 1. Figure 1 The prepared Gd-CDs showed good monodispersity and quasi-spherical morphology, with an average particle size of 1.2-1.4 nm ( Figure 1 a), the lattice spacing is 0.32nm ( Figure 1 b). The smaller size facilitates the carbon dots to enter cells, making cell imaging possible in the next step. Figure 3 The corresponding element distribution pictures of gadolinium-containing carbon dots and carbon dots are shown in Figure 2. Figure 4 The figure is a histogram of the element distribution of gadolinium-containing carbon dots and carbon dots. Compared with pure carbon dots, the content of gadolinium in gadolinium-containing carbon dots is significantly increased, which further illustrates the successful incorporation of gadolinium. In addition, the content of gadolinium in gadolinium-containing carbon dots was determined by ICP-MS, and the results showed that the content of gadolinium was 28.47%.
[0072] In order to characterize the surface functional groups of carbon dots before and after synthesis and before and after gadolinium doping, FT-IR spectroscopy was performed on the raw materials and freeze-dried carbon dots. Figure 2 As shown, 3363cm -1 and 3385cm -1The strong and sharp peak nearby is the characteristic absorption peak of the stretching vibration of the NH bond on the amino group in o-phenylenediamine, but there is no such sharp absorption peak in the carbon dots and gadolinium-containing carbon dots samples, indicating that o-phenylenediamine was successfully oxidized, dehydrated and carbonized into carbon dots. -1 The absorption peaks around 1140 cm-1 correspond to the C=O stretching vibration in the amide bond, indicating that the amide group is well retained after the carbon dots are formed and doped with gadolinium. -1 The peaks on the left and right correspond to the CN stretching vibration peaks of amines. Figure 5 As shown, the 1450 cm -1 and 1660cm -1 The peaks between correspond to the stretching vibration of C=C on the aromatic ring, while no obvious peaks are observed in the gadolinium-containing carbon dots. We speculate that the introduction of gadolinium will destroy the aromatic structure of the carbon dots to a certain extent, which is consistent with the previous fluorescence spectrum, that is, with the increase of gadolinium doping concentration, the fluorescence intensity of the gadolinium-containing carbon dots gradually weakens.
[0073] In order to explore the magnetic resonance imaging capability of gadolinium-containing carbon dots after introduction into the composite material, a 1.2T rat magnetic resonance imaging system was used to test the relaxation time T1 and T1-weighted imaging, and MR images (sagittal plane) were collected for analysis. Figure 7 As shown, Figure 7 a is the gadolinium-containing carbon dots obtained in Example 1 and the Gd 3+ T1-weighted imaging; Figure 7 b is Gd 3+ The longitudinal relaxation rate test of gadolinium-containing carbon dots in ultrapure water. The two-dimensional and three-dimensional images show that compared with the pure polymer material without doping, the material doped with gadolinium-containing carbon dots exhibits obvious imaging brightness, proving that the addition of gadolinium-containing carbon dots can give the composite material excellent nuclear magnetic resonance imaging capabilities, which lays the foundation for subsequent in vivo imaging applications.
[0074] like Figure 8As shown, the fluorescence photos of the gadolinium-containing carbon dots obtained in Example 1 after being doped with the polymer film at different time points in the PBS solution. The instrument used is a small animal live imaging system. Under the excitation of 480nm wavelength, the fluorescence imaging of the material at 600nm is monitored. The doping amount of the gadolinium-containing carbon dots used is 2.5 micrograms / gram, and the control group above is a polymer film not doped with gadolinium-containing carbon dots. Previous fluorescence spectrum tests have shown that gadolinium-containing carbon dots have excellent photoluminescence properties. Using this property, we explored the possibility of using gadolinium-containing carbon dots to monitor material degradation. Through the small animal live imaging system, under the excitation of 480nm wavelength, the fluorescence imaging of the material at 600nm is monitored. The polymer film doped with gadolinium carbon dots shows strong fluorescence, while the pure polymer film has no fluorescence. After incubation in PBS solution for 1 week, the fluorescence intensity of the composite film is significantly reduced, and with the increase of incubation time, the fluorescence intensity gradually weakens. This is because the gadolinium-containing carbon dots in the composite film are gradually released, resulting in a weakening of the fluorescence intensity. Figure 8 The schematic diagram of the fluorescence intensity change is shown in Fig. 9 As shown in the figure, quantitative analysis of fluorescence intensity also shows that within 12 weeks of incubation, the fluorescence intensity of the composite film decreases with time, while the pure polymer film has no fluorescence. The experimental results show that gadolinium-containing carbon dots can give the material excellent fluorescence properties. Based on this fluorescence property, the release behavior of gadolinium-containing carbon dots in the composite material and the degradation of the material can be monitored, which is of great significance for the imaging of biomaterials in vivo and the monitoring of material degradation.
[0075] like Fig.10 As shown, Fig.10 a and Fig.10 b is different concentrations of Gd 3+ Cell survival after co-culture with rat calvarial osteoblasts (ROBs); Fig.10 c and Fig.10 d is the cell survival rate after the carbon dots and gadolinium-containing carbon dots obtained in Example 1 were co-cultured with ROBs. Fig.10 Shows different concentrations of Gd 3+ It has good biocompatibility with rat skull osteoblasts (ROBs), and the cell survival rate remains above 90% when the concentration reaches 1mM. The cytotoxicity test results of carbon dots show that when the concentration of pure carbon dots reaches 200 micrograms / ml, the cell survival rate remains above 80%, and there is no obvious cytotoxicity ( Fig.10 c) After the introduction of gadolinium, the cell compatibility of gadolinium-containing carbon dots was further improved. At a concentration of 1000 μg / ml, the cell survival rate reached more than 90%, proving the excellent cell compatibility of gadolinium-containing carbon dots ( Fig.10 d). More importantly, the gadolinium content was 28.47% as measured by ICP-MS. At the same gadolinium concentration, the cell compatibility of gadolinium-containing carbon dots was higher than that of Gd 3+, which proves that Gd-containing carbon dots effectively reduce the cytotoxicity of Gd, which may be due to the carbon dots 3+ The good cell compatibility lays a foundation for in vivo imaging and bone repair experiments of gadolinium-containing carbon dots.
[0076] Based on the excellent fluorescence properties and good biocompatibility of gadolinium-containing carbon dots, we introduced gadolinium-containing carbon dots into ROBs for in vitro cell imaging experiments. Fig.11 The figure shows the cell imaging images of ROBs by gadolinium-containing carbon dots obtained in Example 1. The instrument used is a fluorescence inverted microscope. The concentration of gadolinium-containing carbon dots used is 200 μg / ml. The images from left to right are fluorescence imaging images under bright field, green light, blue light and ultraviolet excitation, respectively. The control group is cells not co-cultured with the material. The cells co-cultured with Gd-CDs show green and red fluorescence under the excitation of blue (460-500nm) and green (517-563nm) light, respectively, but no fluorescence is observed under the excitation of ultraviolet (340-380nm) light. This is because ultraviolet light exceeds the optimal excitation wavelength range of gadolinium-containing carbon dots, which is consistent with the previous fluorescence spectrum results.
[0077] like Fig.12 As shown, the cell imaging images of ROBs by gadolinium-containing carbon dots obtained in Example 1 were obtained. The instrument used was a laser confocal microscope, and the concentration of gadolinium-containing carbon dots used was 200 micrograms / ml. The pictures from left to right were bright field and fluorescence imaging pictures under 405nm laser excitation, respectively. The control group was cells not co-cultured with the material. The fluorescence spectrum of the cells under 405nm excitation was observed by laser confocal microscopy. The wavelength range of the received signal was set at about 566nm, and obvious fluorescence signals in the cells could be observed. In contrast, cells not treated with gadolinium-containing carbon dots had no fluorescence at the same excitation wavelength. The luminescence of gadolinium-containing carbon dots was mainly concentrated in the cytoplasm region of the cells, while the fluorescence intensity in the cell nucleus was much weaker. More importantly, no light flickering and photobleaching occurred during the fluorescence observation process, which indicates that gadolinium-containing carbon dots have excellent photostability and good application potential in biomedical engineering.
[0078] like Fig.13As shown, the imaging images of zebrafish larvae by gadolinium-containing carbon dots obtained in Example 1 are shown. The instrument used is a fluorescence inverted microscope. The concentration of gadolinium-containing carbon dots used is 50 μg / ml. The images from left to right are fluorescence imaging images under bright field, green light, blue light and ultraviolet excitation, respectively. The control group is a zebrafish larvae not co-cultured with the material. Zebrafish is an important model organism due to its rapid embryonic reproduction ability, short passage time and easy culture. It is highly homologous to mammals and has 70% of human genes orthologous to humans. The characteristics make zebrafish have important value in in vivo imaging, behavioral research and human disease simulation, and have been widely used in biological and biochemical research. Therefore, we chose zebrafish to further explore the biocompatibility, in vivo distribution and imaging effect of gadolinium-containing carbon dots in vivo. The gadolinium-containing carbon dots with a concentration of 50 μg / ml were co-cultured with zebrafish larvae grown to 72 hpf for 4 hours. After washing away the residual carbon dots, the zebrafish was anesthetized and placed under an inverted fluorescence microscope for observation. Fig.13 The results are consistent with cell imaging. Zebrafish larvae co-cultured with gadolinium-containing carbon dots show green and red fluorescence under the excitation of blue and green light, respectively, but no fluorescence is observed under the excitation of ultraviolet light. Zebrafish larvae not treated with gadolinium-containing carbon dots have no fluorescence under the same excitation wavelength. The experimental results confirm that gadolinium-containing carbon dots can enter the zebrafish body through swallowing and skin absorption, and selectively accumulate in the head, yolk sac and tail, indicating that gadolinium-containing carbon dots have tissue-dependent affinity.
[0079] like Fig.14 The figure shows the three-dimensional imaging image of zebrafish larvae by gadolinium-containing carbon dots obtained in Example 1. The instrument used is a laser confocal microscope. The concentration of gadolinium-containing carbon dots used is 50 μg / ml. The upper picture is a bright field picture, and the lower picture is a fluorescence imaging picture under 405nm laser excitation. The 3D fluorescence spectrum of zebrafish under 405nm excitation was observed by laser confocal microscope, which further proves the good imaging ability of gadolinium-containing carbon dots in zebrafish larvae.
[0080] The above describes the embodiments and comparative examples of the present invention in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Any changes, modifications, substitutions or simplifications made according to the spirit and principle of the technical solution of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing a gadolinium-containing carbon dot composite nanomaterial, characterized in that: The following steps are involved: S1: dissolving gadolinium salt and o-phenylenediamine in deionized water to form a mixed solution, and stirring at room temperature for 30 to 60 minutes to make the solution uniform; S2: adding the uniformly mixed solution into a polytetrafluoroethylene reactor and heating it to react, and naturally cooling the solution after the reaction to room temperature to obtain a product solution; S3: The product solution is filtered with a microporous filter membrane in turn, and then dialyzed with a dialysis bag to remove unreacted small molecules, and then freeze-dried to obtain brown-yellow powder-containing gadolinium carbon dots.
2. The method for preparing a gadolinium-containing carbon dot composite nanomaterial according to claim 1, characterized in that: The gadolinium salt in S1 is gadolinium chloride hexahydrate.
3. The method for preparing a gadolinium-containing carbon dot composite nanomaterial according to claim 1, characterized in that: The gadolinium salt concentration of the mixed solution in S1 is 6.2 mg / mL, and the o-phenylenediamine concentration of the mixed solution is 12.6 mg / mL.
4. The method for preparing a gadolinium-containing carbon dot composite nanomaterial according to claim 1, characterized in that: The heating temperature in S2 is 160° C. and the reaction time is 6 hours.
5. The method for preparing a gadolinium-containing carbon dot composite nanomaterial according to claim 1, characterized in that: The pore size of the microporous filter membrane in S3 is 0.22 μm; the molecular weight of the dialysis bag is 500 Da, and the dialysis time is 3 days.
6. A gadolinium-containing carbon dot composite nanomaterial prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The particle size of the gadolinium-containing carbon dot composite nanomaterial is 1.2-1.4 nm.